PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR PADA MATA PELAJARAN IPS POKOK BAHASAN KEBERAGAMAN BUDAYA BANGSAKU KELAS I SD NEGERI 56 KOTA TERNATE - Muhamad, Harmoko (Universitas Khairun, 2024)
This research was conducted with the aim of improving social studies learning outcomes by using image media in the social studies subject, the subject of cultural diversity of my people, for class I students at SD Negeri 56 Ternate City. The type of research used was Classroom Action Research (PTK). This data collection and research technique uses observation sheets, tests and documentation which are used to determine student learning outcomes. The data analysis technique used is quantitative descriptive, which is seen from several percent of the success rate of student learning outcomes.Based on the results of research that has been carried out, it can be concluded that learning using image media can improve social studies learning outcomes, especially material on cultural diversity of my people in class I of SD Negeri 56 Ternate City. This can be seen in the first cycle test, there were 12 students who did not complete the test with an average of 63.63%. Meanwhile, in cycle II there was an increase of 22 students who took part in class learning, 19 students completed it or 86.34% with an average score of 80.90%. Thus the ratio of participants in cycles I and II was 73.69%.